Ok so this question:
y + 1 = - ( x - 2 ) (distribute the negative inside the parenthesis)
y + 1 = -x + 2 (substitute the y= -1)
-1 + 1 = -x + 2
0 = -x + 2 (take two to the other side)
-2 = -x (divide the negative away from x)
2 = x
Answer:
2/(3x-2)²
Step-by-step explanation:
4x²-6x³-2x²+6x³/4x²-6x³-6x³+9x^4=
2x²/4x²-12x³+9x^4=
2x²/x²(4-12x+9x²)=
2/9x²-12x+4
2/(3x-2)²
Answer:
x=12
Step-by-step explanation:
Let the integers be x - 1, x and x + 1, then
x - 1 + x + x + 1 = -42
3x = -42
x = -42/3 = -14
The three consectutive integers are -15, -14 and -13
Answer:
could you possibly zoom in
Step-by-step explanation: